Losing reality : on cults, cultism, and the mindset of political and religious zealotry - Lifton, Robert Jay, 1926- (The New Press, 2019)
"A definitive account of the psychology of zealotry, from a National Book Award winner and a leading authority on the nature of cults, political absolutism, and mind control"-- Provided by publisher
Keywords: Fanaticism.; Brainwashing.; Cults.; Religion and politics.; Fanatisme.; Lavage de cerveau.; Religion et politique.; MEDICAL -- Neuroscience.; Brainwashing; Cults; Fanaticism; Religion and politics; SOCIAL SCIENCE / Sociology / Social Theory